Vapor-Liquid Equilibrium Data for The Binary Systems of Methacrylic Acid, Methyl Methacrylate, and Water at 26 kPa and 50 kPa - Zauziah Pramiswari Putri (Jurnal Syntax Transformation, 2025)
Methyl methacrylate (MMA) is a significant organic compound utilized across diverse industrial sectors. This research study aims to examine the separation of azeotropic systems containing MMA derived from the C4 route. The primary focus of this examination is on vapor-liquid equilibrium (VLE) data for binary systems of methacrylic acid (MAA) and water, as well as methacrylic acid and MMA. The study will be conducted under vacuum pressures of 26 kPa and 50 kPa. The objective of this study is to generate and analyze VLE data, thereby facilitating a comprehensive understanding of the azeotropic behavior and non-ideal interactions in these systems. The VLE data were obtained using a modified Rose-Williams type recirculation still. The azeotropic composition of the methacrylic acid and water system was confirmed, and the data were validated through Herrington and van Ness methods to ensure thermodynamic consistency. The findings indicate that the excess of the calculated Gibbs free energy and activity coefficient substantiates the non-ideal behavior. In conclusion, this study provides valuable insights into the design and optimization of the MMA by-product separation process. To further refine the model and enhance its predictive capabilities, additional research is recommended, focusing on exploring the impact of diverse experimental conditions and evaluating the efficacy of alternative predictive models.